Comparative analysis of surgical interventions for postoperative ventral hernia in obese patients - Kravchenko , B.S.; Klimenko, A.V.; Klimenko , V.N.; Sergееva , L.N. (Medicni Perspektivi, 2021)
The problem of surgical treatment of postoperative ventral hernias remains relevant today. Currently, a large number of methods of surgical interventions for hernias of the anterior abdominal wall have been proposed, the variety of which requires systematization and analysis of the immediate and distant results of treatment. Goal: to analyze the effectiveness of laparoscopic hernia repair in patients with postoperative ventral hernia with a body mass index of 30 kg/m2. The results of treatment of 29 patients with postoperative ventral hernia were analyzed. Men – 8 (27.5%), women – 21 (72.5%). In 16 (55.2%) patients (main group) laparoscopic intraperitoneal onlay mesh – IPOM was performed, in 13 (44.8%) patients (comparison group) open hernia repair with fixation of the mesh graft in the Sublay position was performed. The analysis of the duration of the surgical intervention indicates that with open hernia repair, there is a significant increase in the duration of the surgical intervention, p˂0.0001. Comparison of the duration of operations in both groups depending on the body mass index also indicates the dependence of the duration of surgery on this indicator. Thus, in the comparison group, there was a tendency to an increase in the duration of the operation with an increase in the body weight of patients with a significant difference in the duration of the operation between the main group and the comparison. The duration of a patient's stay in the hospital and the occurrence of respiratory complications correlates with the level of postoperative pain and the duration of surgery. Postoperative complications in the form of fluid accumulations in the wound area of the abdominal wall depend on the method of surgery and the location of the mesh graft. The use of laparoscopic – IPOM in obese patients significantly improves the results of surgery by reducing the level of postoperative pain, shortening the duration of surgery, and the absence of complications in the early and late postoperative period. When choosing the method of surgical intervention in patients with postoperative ventral hernia, laparoscopic IPOM should be preferred.